Chinese Fishes - Noakes, David L. G.; Romero, Aldemaro; Zhao, Yahui; Zhou, Yingqi; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This book documents the current state of research by Chinese scientists on fish biology and fisheries and brings together manuscripts by authors from research institutions, universities and government agencies. There are papers on aquaculture, life history, genetics, marine and freshwater biology, conservation, physiology, new species descriptions, and truly amazing hypogean fishes. The information on these remarkable cave species shows how much we have yet to learn from that incredible fauna. There are papers dealing with some of the largest fishes and some of the smallest cave species. There are papers dealing with some of the most traditional forms of aquaculture and others with the most modern molecular techniques. The volume includes papers on critically threatened native fishes as well as the most common food species, such as grass carp (Ctenopharyngodon idella). The information on rare and threatened species shows how China is dealing with their endangered fishes. The information on their carp species will be invaluable to those in other countries who will either take advantage of the productive carp species in aquaculture or try to manage them as invasive species outside China. For the first time we bring together a complete overview of the state of fisheries research in China.
Introducing China -- Threatened fishes of the world: Brachymystax lenok tsinlingensis Li, 1966 (Salmonidae) -- Changes in abundance of larvae of the four domestic Chinese carps in the middle reach of the Yangtze River, China, before and after closing of the Three Gorges Dam -- The fish fauna of mountain streams in the Guanshan National Nature Reserve, Jiangxi, China -- Threatened fishes of the world: Schizothorax taliensis Regan, 1907 (Cyprinidae) -- A review of the genus Distoechodon (Teleostei: Cyprinidae), and description of a new species -- Otolith microstructure of Oxygymnocypris stewartii (Cypriniformes, Cyprinidae, Schizothoracinae) in the Lhasa River in Tibet, China -- Otolith characteristics and age determination of an endemic Ptychobarbus dipogon (Regan, 1905) (Cyprinidae: Schizothoracinae) in the Yarlung Tsangpo River, Tibet -- Threatened fishes of the world: Trachidermus fasciatus Heckel, 1837 (Cottidae) -- Detection of hybridization between two loach species (Paramisgurnus dabryanus and Misgurnus anguillicaudatus) in wild populations -- Threatened fishes of the world: Onychostoma alticorpus (Oshima, 1920) (Cyprinidae) -- Age composition, growth, and reproductive biology of yellow catfish (Peltobagrus fulvidraco, Bagridae) in Ce Lake of Hubei Province, Central China -- The reproductive traits of brown trout (Salmo trutta fario L.) from the Yadong River, Tibet -- Age structure, growth and mortality estimates of an endemic Ptychobarbus dipogon (Regan, 1905) (Cyprinidae: Schizothoracinae) in the Lhasa River, Tibet -- Threatened fishes of the world: Gobiocypris rarus Ye and Fu, 1983 (Cypinidae) -- Degradation of icefishes (Salangidae) in the Yangtze River basin of China: threats and strategies -- Threatened fishes of the world: Yunnanilus discoloris Zhou & He 1989 (Cobitidae) -- Feeding, morphological changes and allometric growth during starvation in miiuy croaker larvae -- Isolation of cellulose$1 (Bproducing microbes from the intestine of grass carp (Ctenopharyngodon idellus) -- Sinocyclocheilus guilinensis, a new species from an endemic cavefish group (Cypriniformes: Cyprinidae) in China -- Threatened fishes of the world: Squalidus iijimae (Oshima, 1919) (Cyprinidae) -- Comparative and evolutionary analysis in natural diploid and tetraploid weather loach Misgurnus anguillicaudatus based on cytochrome b sequence data in central China -- Age and growth of Schizopygopsis younghusbandi younghusbandi in the Yarlung Zangbo River in Tibet, China -- Threatened fishes of the world: Sinocyclocheilus anophthalmus (Chen and Chu, 1988) (Cyprinidae) -- The taxonomy and phylogeny of the cyprinid genus Opsariichthys Bleeker (Teleostei: Cyprinidae) from Taiwan, with description of a new species -- Hemimyzon sheni, a new species of balitorid fish (Teleostei: Balitoridae) from Taiwan -- Subspecies validity for genus Culter (Teleostei: Cyprinidae) based on morphometrics analysis -- A new cavefish species, Sinocyclocheilus brevibarbatus (Teleostei: Cypriniformes: Cyprinidae), from Guangxi, China -- The Hypogean fishes of China.s
Keywords: Environmental sciences; Aquatic biology; Conservation biology; Evolution (Biology).; Vertebrates; Marine Sciences; Environment; Marine & Freshwater Sciences; Freshwater & Marine Ecology; Conservation Biology/Ecology.; Evolutionary Biology; Vertebrates